2019
DOI: 10.3389/fmicb.2019.01169
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding Insights Into the Trophic Behavior and Identity of Intertidal Benthic Foraminifera

Abstract: Foraminifera are ubiquitous marine protists with an important role in the benthic carbon cycle. However, morphological observations often fail to resolve their exact taxonomic placement and there is a lack of field studies on their particular trophic preferences. Here, we propose the application of metabarcoding as a tool for the elucidation of the in situ feeding behavior of benthic foraminifera, while also allowing the correct taxonomic assignment of the feeder, using the V9 region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 101 publications
6
42
0
Order By: Relevance
“…However, bacterial uptake by benthic foraminifera has been shown to be unselective, implying that bacterivory occurs mainly in association with potential deposit-feeding behaviour 21 . Feeding strategies, as well as organic matter turnover rates, appear to be species-specific 2123 . For example, in situ experiments with 15 N labelled bacteria have shown that benthic foraminifer Ammonia tepida prefers algae in its diet over bacteria 24 , suggesting that bacteria are not its primary food source.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, bacterial uptake by benthic foraminifera has been shown to be unselective, implying that bacterivory occurs mainly in association with potential deposit-feeding behaviour 21 . Feeding strategies, as well as organic matter turnover rates, appear to be species-specific 2123 . For example, in situ experiments with 15 N labelled bacteria have shown that benthic foraminifer Ammonia tepida prefers algae in its diet over bacteria 24 , suggesting that bacteria are not its primary food source.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in situ experiments with 15 N labelled bacteria have shown that benthic foraminifer Ammonia tepida prefers algae in its diet over bacteria 24 , suggesting that bacteria are not its primary food source. In addition to bacterivory, foraminifera are known to have a variety of other feeding strategies, such as herbivory, carnivory and even direct dissolved organic carbon uptake 21,23,25,26 . Mixotrophy is also an important trophic strategy for some shallow-water benthic foraminifera with the ability to harbour photosymbionts or kleptoplasts 2729 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foraminifera exhibit a large range of feeding strategies, some are selective feeders (Muller, 1975;Suhr et al, 2003;Chronopoulou et al, 2019). Hagens et al (2015) reported that in Lake Grevelingen the phytoplankton composition was different between spring and summer 2012.…”
Section: Species-specific Response To Environmental Conditions In Lakmentioning
confidence: 99%
“…seems able to feed on very diverse food sources including microalgae, diatoms, bacteria or even metazoans (Lee et al, 1969;Moodley et al, 2000;Dupuy et al, 2010;Jauffrais et al, 2016;Chronopoulou et al, 2019). Recently, Chronopoulou et al (2019) showed different feeding preferences for Ammonia sp. T6 and E. selseyense in intertidal environments in the Dutch Wadden Sea.…”
Section: Species-specific Response To Environmental Conditions In Lakmentioning
confidence: 99%